2011
DOI: 10.1139/h10-111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eccentric exercise velocity on akt/mtor/p70s6ksignaling in human skeletal muscle

Abstract: It has been suggested that muscle tension plays a major role in the activation of intracellular pathways for skeletal muscle hypertrophy via an increase in mechano growth factor (MGF) and other downstream targets. Eccentric exercise (EE) imposes a greater amount of tension on the active muscle. In particular, high-speed EE seems to exert an additional effect on muscle tension and, thus, on muscle hypertrophy. However, little is known about the effect of EE velocity on hypertrophy signaling. This study investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
1
12
0
2
Order By: Relevance
“…have shown that MSCs-derived exosomes could increase ATP levels, decrease oxidative stress and activate PI3K/Akt pathway to enhance myocardial viability and prevent adverse remodeling via increasing glycolysis after myocardial ischemia/reperfusion injury 15 . Moreover, previous studies on mTOR signal transduction pathway have revealed positive effects on skeletal muscle regeneration 16 17 18 19 . Considering mTOR signal pathway controls protein synthesis in different levels by increasing the translation of certain mRNAs, we hypothesize here that the activation of mTOR signal transduction pathway by paracrine action of BM-MSCs after myocardial infarction, will further increase cardiomyocyte protein synthesis and glucose metabolism, and then improve systolic function of heart.…”
mentioning
confidence: 99%
“…have shown that MSCs-derived exosomes could increase ATP levels, decrease oxidative stress and activate PI3K/Akt pathway to enhance myocardial viability and prevent adverse remodeling via increasing glycolysis after myocardial ischemia/reperfusion injury 15 . Moreover, previous studies on mTOR signal transduction pathway have revealed positive effects on skeletal muscle regeneration 16 17 18 19 . Considering mTOR signal pathway controls protein synthesis in different levels by increasing the translation of certain mRNAs, we hypothesize here that the activation of mTOR signal transduction pathway by paracrine action of BM-MSCs after myocardial infarction, will further increase cardiomyocyte protein synthesis and glucose metabolism, and then improve systolic function of heart.…”
mentioning
confidence: 99%
“…However, Tamaki's exercise mode does not optimize the eccentric phase of the lifts. In humans, maximal eccentric contractions are reported to be effective in stimulating mTOR and p70 S6K1 via an Akt-independent pathway 18,19. This effect may be mediated by a combination of greater tension and stretching of the skeletal muscles during the descending phase of the lift.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects performed five sets of 8 repetitions of a slow or fast eccentric protocol and biopsies were collected at the following time intervals: baseline, immediately after, and two hours after the session. MGF expression was increased approximately 2.5 fold in slow eccentric contraction, and Akt and p70 s6K protein phosphorylation were higher in the fast eccentric protocol than at baseline, or slow or fast eccentric contraction, which suggests that the velocity has no direct influence on the activation of this pathway, and other signaling pathways could be selectively activated and involved in the response to high velocity eccentric contraction [62].…”
Section: Exercise Training and The Akt-mtor Pathwaymentioning
confidence: 92%